2021
DOI: 10.1007/s11606-021-07066-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors of Respiratory Failure in a Cohort of Young Patients Requiring Hospital Admission with SARS-CoV2 Infection in Spain: Results of the Multicenter SEMI-COVID-19 Registry

Abstract: Background Age is a risk factor for COVID severity. Most studies performed in hospitalized patients with SARS-CoV2 infection have shown an over-representation of older patients and consequently few have properly defined COVID-19 in younger patients who require hospital admission. The aim of the present study was to analyze the clinical characteristics and risk factors for the development of respiratory failure among young (18 to 50 years) hospitalized patients with COVID-19. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…According to previous reports, older age, male sex, presence of comorbidities including hypertension, CVD, COPD, CKD, cancer and immunosuppression were more common in patients deceased, probably as a result of more severe disease and higher rates of respiratory failure requiring intubation and ICU admission [3,4,[20][21][22][23][12][13][14][15][16][17][18][19]. With regard to comorbidities, the results of this study revealed an association of CKD and immunosuppression with COVID-19 related mortality as previously reported [17,[24][25][26].…”
Section: Administrated Therapies During Hospitalizationmentioning
confidence: 99%
“…According to previous reports, older age, male sex, presence of comorbidities including hypertension, CVD, COPD, CKD, cancer and immunosuppression were more common in patients deceased, probably as a result of more severe disease and higher rates of respiratory failure requiring intubation and ICU admission [3,4,[20][21][22][23][12][13][14][15][16][17][18][19]. With regard to comorbidities, the results of this study revealed an association of CKD and immunosuppression with COVID-19 related mortality as previously reported [17,[24][25][26].…”
Section: Administrated Therapies During Hospitalizationmentioning
confidence: 99%
“…Several previous studies have published clinical scores that attempt to predict the risk of worse outcomes in patients with COVID-19 [ 16 , 17 , 24 28 ]. However, some of these studies have methodological limitations, including small patient samples, an unrepresentative selection of the control group, or short or incomplete follow-up periods [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over 24,000 patients over 18 years of age were included. Several studies derived from the SEMI-COVID-19 Registry have reported clinical characteristics with prognostic value [ 4 , 14 16 ] as well as prognostic scores [ 17 , 18 ]. However, since the start of the pandemic, multiple factors have changed the course of disease because the clinical management [ 20 ], available resources, and treatments indicated have evolved since the beginning of the pandemic [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early in the COVID-19 pandemic, rates of alcohol use disorders (AUDs) accelerated for multiple reasons including increased isolation, use of alcohol as a coping mechanism, and lack of readily available abstinence resources (1–3). Prior investigations have demonstrated dose-dependent associations between alcohol misuse and poorer outcomes in patients hospitalized with pneumonia including increased risk for prolonged hospital and ICU lengths of stay and development of the acute respiratory distress syndrome (ARDS) (4–15). While changes in alcohol consumption have been consistently observed during the COVID-19 pandemic, the impact of alcohol misuse on healthcare outcomes related to COVID-19 are conflicted.…”
mentioning
confidence: 99%
“…Prior investigations have demonstrated dose-dependent associations between alcohol misuse and poorer outcomes in patients hospitalized with pneumonia including increased risk for prolonged hospital and ICU lengths of stay and development of the acute respiratory distress syndrome (ARDS) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). While changes in alcohol consumption have been consistently observed during the COVID-19 pandemic, the impact of alcohol misuse on healthcare outcomes related to COVID-19 are conflicted.…”
mentioning
confidence: 99%